2018
DOI: 10.1186/s13643-018-0861-z
|View full text |Cite
|
Sign up to set email alerts
|

CYP genetic variants and toxicity related to anti-tubercular agents: a systematic review and meta-analysis

Abstract: BackgroundTreatment with anti-tuberculosis drugs may cause patients to experience serious adverse effects. Genetic factors, such as polymorphisms of CYP genes, may increase the likelihood of a patient experiencing such adverse drug reactions. In this systematic review and meta-analysis, we synthesised evidence for associations between CYP genetic variants and anti-tuberculosis drug-related toxicity outcomes.MethodsWe searched MEDLINE, PubMed, EMBASE, BIOSIS and Web of Science to identify relevant studies. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…EMB binds to TetR, a transcriptional regulator that enhances the INH sensitivity of the inhA gene and leads to increases in the killing effect of INH, thus increasing INH toxicity (Zhu et al, 2019). Genetic polymorphisms in drug metabolic enzyme-encoded genes, such as GST, CYP, and UGT, could affect the risk of EMB hepatotoxicity (Li et al, 2013;Richardson et al, 2018;Sun et al, 2019). Meta-analysis study which conducted on various middle-and high income countries prove that there are significant association between RsaI and 96-bp deletion-insertion SNPs of the CYP2E1 Frontiers in Genetics frontiersin.org gene to the hepatotoxicity (Richardson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMB binds to TetR, a transcriptional regulator that enhances the INH sensitivity of the inhA gene and leads to increases in the killing effect of INH, thus increasing INH toxicity (Zhu et al, 2019). Genetic polymorphisms in drug metabolic enzyme-encoded genes, such as GST, CYP, and UGT, could affect the risk of EMB hepatotoxicity (Li et al, 2013;Richardson et al, 2018;Sun et al, 2019). Meta-analysis study which conducted on various middle-and high income countries prove that there are significant association between RsaI and 96-bp deletion-insertion SNPs of the CYP2E1 Frontiers in Genetics frontiersin.org gene to the hepatotoxicity (Richardson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic polymorphisms in drug metabolic enzyme-encoded genes, such as GST, CYP, and UGT, could affect the risk of EMB hepatotoxicity (Li et al, 2013;Richardson et al, 2018;Sun et al, 2019). Meta-analysis study which conducted on various middle-and high income countries prove that there are significant association between RsaI and 96-bp deletion-insertion SNPs of the CYP2E1 Frontiers in Genetics frontiersin.org gene to the hepatotoxicity (Richardson et al, 2018). The results of a study on the GSTM1 gene polymorphism (null genotype) showed that the polymorphism was associated with hepatotoxic risk in the EMB-containing regimen, while the non-EMB-containing regimen showed insignificant results.…”
Section: Discussionmentioning
confidence: 99%
“…For these genes, conflicting results have been published. Considering recent meta-analyses, two support the roles of CYP2E1, GSTM1, and GSTT1 in AT-DILI [ 19 , 20 ], one does not implicate GSTT1 [ 21 ], and in another CYP2E1 could only be implicated in East Asian populations [ 18 ]. In a trans-ethnic meta-analysis from Nicoletti et al, CYP2E1 was not associated with AT-DILI [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cytochrome P450 2E1 (CYP2E1) is a phase I metabolizing enzyme that converts INH subproducts hydrazine and acetyl hydrazine into reactive hepatotoxic metabolites [ 17 ]. The SNP rs2031920, a 2Kb gene upstream variant, has been associated with higher enzymatic activity [ 18 , 19 ]. Glutathione S-Transferases (GSTs) are phase II metabolizing enzymes with an important role in the detoxification of metabolites resulting from the biotransformation of xenobiotics by phase I enzymes [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence indicates that lncRNA polymorphisms may also be potential biomarkers used for early diagnosis, monitoring therapy response, and prognostic assessment including for TB (45,46). Since results of current pharmacogenomics studies on ATDH are still lacking consistency according to different races, drug dosages, and treatment protocol, the results may not be representative of a Chinese population infected with TB (31,32,(47)(48)(49). Considering China's heavy burden of TB, further pharmacogenetic studies aiming to identify novel potential targets are needed in order to provide a better understanding of the potential mechanism of ATDH and optimize treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%